Collaborative Environment as a Means of Forming Success of a Future Teacher of Elementary Classes in Project Activity - Syzdykbayeva, Aigul D.; Mambetalina, Aliya S.; Nuradinov, Almat S.; Kurmanbekova, Manshuk B.; Kabylbekova, Zauret B. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The purpose of the study is to determine whether future elementary school teachers are successful in project activities and whether a properly organised collaborative environment affects the outcome of project activities. Background: In conditions when a person is the most important value and main capital of a society, the goal and product of the educational system should be human intelligence and personality. Therefore, for domestic education today, the issue of raising the status of the teaching profession and the modernisation of teacher education has become serious. The article reveals the problem of the successful formation of a future primary school teacher in project activities through a collaborative environment. The authors define the concepts of "project activity", "the success of the future primary school teacher in project activity”, “project”, “collaborative environment”. Method: The methodology for organising a collaborative environment in project activities is determined. The study involved two groups; the sample was 107 pupils. Results: A programme for diagnosing the successful formation of a future primary school teacher in project activities is presented. Criteria, indicators (motivational, cognitive, activity) and levels of success formation of the future primary school teacher in project activities (intuitive, reproductive, creative) are defined. Conclusion: As part of the study, the authors determined that a collaborative environment is an effective means of success for a future primary school teacher in design. A collaborative environment was defined as the collaboration of a teacher and pupils in solving a problem, completing a task, or creating a product.